Cytokinin and auxin levels in micropropagating Red Fuji and McIntosh apple varieties - Magyarné Tábori, Katalin; Dobránszki, Judit; Ferenczy, Antal; Jámborné Benczúr, Erzsébet; Lazányi, János (Acta Agraria Debreceniensis, 2001)
Effects of media hormone content on in vitro shoot multiplication and rooting were examined in cv. Red Fuji and McIntosh apple scions. Multiplication responses of shoots to different concentrations (0.5 and 1.0 mg/l) of 6-benzylaminopurine and 6-benzylaminopurine riboside were tested at two levels (0.1 and 0.3 mg/l) of indole-3-butyric acid. The best proliferation rate was achieved on medium containing 1.0 mg/l 6-benzylaminopurine and 0.1 mg/l indole-3-butyric acid in cv. Red Fuji (5.3) and on medium containing 1.0 mg/l 6-benzylaminopurine and 0.3 mg/lindole-3-butyric acid in cv McIntosh (10.3). The length of shoots on these media was enough for rooting (38.4 mm in cv. Red Fuji and 39.3 mm in cv McIntosh). Shoots developed on the best proliferation medium were used for rooting. Effects of different concentrations of auxin in the root induction media and presence of activated charcoal in the root elongation media were examined on rooting capacity. The best rooting rate (100% in cv. McIntosh and 83% in cv. Red Fuji) was achieved when the root induction medium contained 1.0 mg/l indole-3-butyric acid. In general, rooting was inhibited in the presence of activated charcoal.  Because of high in vitro multiplication and rooting rate and high percent of survival during acclimatisation, the methods described here make effective micropropagation processes possible for cv. Red Fuji and McIntosh.